Pemberdayaan Guru Pendidikan Anak Usia Dini melalui Platform Merdeka Mengajar: Peluang dan Tantangan di Era Digital - Sumiyem; Edi Waluyo; Yuli Utanto (Jurnal Penelitian Pendidikan IPA, 2025)
The study aimed to analyze the utilization of the Merdeka Mengajar Platform (PMM) among Early Childhood Education (ECE) teachers in Semarang City and to identify factors influencing its adoption. A mixed-methods approach with a sequential explanatory design was employed, combining a quantitative survey of 100 teachers and qualitative interviews with 10 selected participants. Quantitative data were analyzed using descriptive and regression analyses, while qualitative data were examined through thematic analysis to explore teachers’ experiences in depth. The results showed that PMM utilization was at a moderate-high level, with teachers primarily using the platform for accessing teaching resources and curriculum development. Regression analysis indicated that digital literacy (β = 0.45, p < 0.001) and infrastructure support (β = 0.32, p = 0.003) significantly influenced PMM utilization, explaining 52% of the variance. Qualitative findings revealed three dominant themes: empowerment through PMM, barriers to optimal use, and the need for continuous institutional support. The study concludes that effective PMM adoption requires not only technological readiness but also sustained digital mentoring and institutional facilitation. These findings contribute to strengthening teacher professionalism and digital competence within the framework of Indonesia’s Merdeka Curriculum